Investigation of business client’s behaviour in the context of price demand elasticity - Chalupa, Stepan; Petricek, Martin; Chadt, Karel (Journal of Tourism Management Research, 2025)
The study’s primary purpose is to investigate the behavior of business clients by measuring their coefficient of price elasticity of demand. Many revenue management studies describe this segment as price inelastic without empirical evidence. The paper uses an econometric approach to estimate the customers’ reactions to pricing strategies. Log-log regression models based on OLS were used to figure out the coefficient of price demand elasticity. The data came from 9343 reservations made by business travelers that were taken from the property management system. Contrary to previous expectations and estimates, the findings show that business travelers are becoming more price-sensitive. The demand is price elastic for shorter stays of 2-3 nights (Epd=-1,121) or reservations from the business OTAs (Epd=-1,030). Most previous studies thought that business travelers wouldn’t care about price and wouldn’t be interested in online dynamic strategies. This study shows that their behaviour has changed. Contrary to previous revenue management studies, we propose widening the scope of their online activities to business clients who tend to be more flexible. Revenue management optimization processes might directly adopt the study’s results. Hoteliers should include business clients in their dynamic pricing strategies.